THE EFFECT OF POSITION ANALYSIS ON EMPLOYEE PERFORMANCE WITH JOB SATISFACTION AS AN INTERVENING VARIABLE (Case Study of Employees of the District Civil Service Agency Serdang Bedagai) - Ghazali Syamni; Harley Agustian; Suci Puji Suryani; Zahrul Fuadi (Universitas Efarina, 2023)
In this study, the population was the Serdang Bedagai District Civil Service Agency, namely 30 people. Because the target population is less than 100, the sampling technique used is the census method, where the entire population, totaling 30 people from the Serdang Bedagai Regency Regional Civil Service Agency, will be used as the research sample. the first hypothesis is accepted, meaning that the Job Analysis variable (X) has a positive and significant effect on Job Satisfaction (Y1). the second hypothesis is accepted, meaning that Job Analysis (X) has a significant effect on Employee Performance (Y2). the third hypothesis is accepted, meaning that Job Satisfaction (Y1) has a positive and significant effect on Employee Performance (Y2).